Pelaksanaan Pendampingan Catin Untuk Mencegah Stunting Dengan Skrinning Status Gizi Dan Indeks Masa Tubuh (Tagindas) - Anggraeny Nawiza, Retno; Yunita, Laurensia; Irawan, Angga (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Chronic lack of energy is a major cause of stunting. Based on the results of a preliminary study conducted in November 2022 in the working area of the Salam Babaris Health Center, Tapin District, data on the total number of catin as many as 86 people were obtained. Researchers conducted an examination with 10 catin people found that 4 catin people had nutritional status (lila measurement) below normal size and body mass index with thin classification. The purpose of the study was to determine the implementation of catin (bride-to-be) assistance to prevent stunting by screening nutritional status and body mass index (TAGINDAS) in the work area of the Salam Babaris Health Center in 2022. Type of descriptive research with cross sectional design, univariate analysis test. Total sampling technique. The sample amounted to 32 catin people. The results of the study showed that most respondents of catin (bride-to-be) health status to prevent stunting were not at risk of stunting as many as 21 people (65.6%), respondents in the nutritional status category were not at risk as many as 21 people (65.6% and most respondents in the normal BMI category were 18 people (56.3%).